MultiMedia modeling : 25th International Conference, MMM 2019, Thessaloniki, Greece, January 8?11, 2019, Proceedings.: 25th International Conference, MMM 2019, Thessaloniki, Greece, January 8?11, 2019, Proceedings. Part I (2019) - Unknown
No abstract available